Harmonic Simulation of Distribution Transformers Due to the Connection Groups - Inan, Aslan; Saglam, Hakan (GAZI UNIV, 2010)
Harmonics which is the most important part of the power quality, development of technology with necessity and increasing usage of power electronics and semi conductor devices, is coming to existence an important problem. An important consideration when evaluating the impact of harmonics is their effect on power system component and loads. Transformers are major components in power systems. The major effects of harmonics on the transformers are additional heating losses, shorter insulation lifetime, lower capacity. In this study the effects of Dyn1, Dyn11 and Yyn connection groups of distribution transformers to the harmonic phenomenon are targeted and for different cases in a MV/LV system with nonlinear load composition modeled with MATLAB Simulink, this effects are viewed.
Keywords: Power quality; harmonics; distribution transformers; winding connection group; Engineering